2018
DOI: 10.1016/j.nicl.2017.10.009
|View full text |Cite
|
Sign up to set email alerts
|

EEG oscillations during word processing predict MCI conversion to Alzheimer's disease

Abstract: Only a subset of mild cognitive impairment (MCI) patients progress to develop a form of dementia. A prominent feature of Alzheimer's disease (AD) is a progressive decline in language. We investigated if subtle anomalies in EEG activity of MCI patients during a word comprehension task could provide insight into the likelihood of conversion to AD. We studied 25 amnestic MCI patients, a subset of whom developed AD within 3-years, and 11 elderly controls. In the task, auditory category descriptions (e.g., ‘a type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
63
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(78 citation statements)
references
References 58 publications
(98 reference statements)
8
63
0
Order By: Relevance
“…We focused our behavioral analysis on learning and memory, because these cognitive functions are severely impaired by AD, and our electrophysiological analysis on electroencephalographic (EEG) recordings, because such recordings can be readily obtained also in humans. Indeed, various types of neural network dysfunction have been detected by EEG in AD patients [57][58][59][60][61][62][63] and related mouse models [53,54,60,[64][65][66][67][68]. We are particularly interested in non-convulsive epileptiform activity, because we and others recently showed that this activity is more prevalent in AD patients than is widely recognized [57,58,60,62,63], its detection predicts faster cognitive decline in AD [63], it could promote disease progression through multiple mechanisms [69], and the relationship between epileptiform activity and APP/Aβ is a matter of debate [26,70].…”
Section: Introductionmentioning
confidence: 99%
“…We focused our behavioral analysis on learning and memory, because these cognitive functions are severely impaired by AD, and our electrophysiological analysis on electroencephalographic (EEG) recordings, because such recordings can be readily obtained also in humans. Indeed, various types of neural network dysfunction have been detected by EEG in AD patients [57][58][59][60][61][62][63] and related mouse models [53,54,60,[64][65][66][67][68]. We are particularly interested in non-convulsive epileptiform activity, because we and others recently showed that this activity is more prevalent in AD patients than is widely recognized [57,58,60,62,63], its detection predicts faster cognitive decline in AD [63], it could promote disease progression through multiple mechanisms [69], and the relationship between epileptiform activity and APP/Aβ is a matter of debate [26,70].…”
Section: Introductionmentioning
confidence: 99%
“…, to capture movement-intentions (Wolpaw et al, 1991;Lotte et al, 2007;Tangermann et al, 2008). For biomarkers applications, the focus is on predicting medical diagnosis and other clinical endpoints Sami et al, 2018;Mazaheri et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Physical and mental tiredness, increased stress level and a need for multitasking negatively influences the capacity of the working memory and therefore the execution of everyday tasks ( 20 ). It is worth remembering that for a person with memory impairments most of the activities, even if typically automatic, constantly remain in the loop of active and conscious processing ( 21 23 ). Otherwise the less significant steps of the executive action are forgotten or performed inadequately.…”
Section: Introductionmentioning
confidence: 99%